Solus Per Aqua (SPA) Massage to Reduce Complaints During the Period Postpartum at Mombykids Village Sambong Dukuh District Jombang Regency Jombang - Henny Sulistyawati (STIKes Patria Husada Blitar, 2021)
The mother's struggle after giving birth takes a long time. One of them is to restore a fresher and more relaxed body shape.Because it cannot be denied, after birth the body will feel weak because of the energy released.The muscles that feel are usually tense, especially for women who give birth normally.This condition is of course intolerable, special care is needed to restore the mother's body to recovery.Solus Per Aqua (SPA) postpartum is one way to restore body shape.Solus Per Aqua (SPA) massage can be useful to improve blood circulation and restore the body to be firmer and make the body more comfortable and relaxed.This study aims to determine the Solus Per Aqua (SPA) Massage in mothers can reduce complaints during postpartum.The type of this research is quasi-experimental using a pretest and posttest design by treating the research subject.The samples in this study were 20 mothers who came to Mombykids from day 2 to 14.The sampling technique used simple random sampling.The variables in this study were spa massage and complaints during postpartum.Data collection was carried out usingÂ checklist and questionnaire.Data processing was performed using the